Molecular analysis of the camp- response element [CRE] elements in the promoter region and exon 1 of the survival of motor neuron 2 [SMN2] gene in Malaysian spinal muscular atrophy patients; to elucidate their role in circumscribing the clinical severity of SMA - Amin Baig, Atif; Y.Y., Chan; Manickam, Ravichandran (2014)
Objective: In the Spinal muscular atrophy [SMA] genes [SMN1 and SMN2 genes]; the CRE-II elements at -400 bp in the promoter region of the SMN genes and CRE-I element at +108 bp in the exon 1 of the SMN genes, are reported to have a role in c-AMP induce expression of the SMN genes through its binding affinity to CREB-1. This study was designed to determine the role of CRE sites in the circumscribing the clinical severity of SMA.